Effectiveness of Planned Teaching Program Regarding Malnutrition on Mother of Children between 6 Months and 36 Months in Urban Area - Joseph, Amita; Batra, Bharati (International Journal of Nursing Research, 2023)
Introduction: Malnutrition is a worldwide problem today. The main target of undernutrition is the preschooler, pregnant, and nursing mothers. It is estimated that about 170 million children “under-five” year of age, i.e., 30% of worlds children are malnourished in terms of being underweight, over 2/3rd of these malnourished children belong to Asia. Aim: A study to assess the effectiveness of planned teaching program on the knowledge of mothers of 6–36-month children on malnutrition in selected Anganwadi of Indore. Materials and Methods: This was a community-based study compromising of 50 mothers purposively selected. Data were collected by administering structured knowledge questionnaire and after that planned teaching program and post-test was taken after 7 days. Results: The total mean of pre-test was 9.5. Most of the subject had 32 (64%) average knowledge and 5 (10%) subjects have good and only 13 (26%) belong to poor. After administration of planned teaching program regarding malnutrition, the total mean of post-test was 14.06. This shows that there is gain in knowledge. Most of the subject that is 7 (14%) average remaining respondent had good knowledge 43 (86%). The mean post-test knowledge is 14.06 which is higher than pretest 9.5, the actual gain of knowledge is 4.56 and computed‘t’ value (t50= 15.39) is more than tabled value (t50= 1.671) at the level of 0.05 thus indicated highly significant difference. Conclusion: The finding of this study indicates that planned teaching program on malnutrition appears to be effective in improving knowledge and practice of mothers of 6–36-month children relating to feeding and caring behaviors. Increase in the knowledge definitely showed a positive effect on the health of the child.